Alternative Fuels The Future of Hydrogen. - Hordeski, Michael Frank (CRC Press [Imprint] Taylor & Francis Group Taylor & Francis Group [distributor], 2008)
Newly revised, the second edition of this pioneering work addresses emerging factors affecting energy production and use, including the availability and desirability of various fuels. The text provides extensive discussion on hydrogen sources, both solar and nuclear, and fuel cell technology, as well as other alternative fuels such as biomass, and wind power. It delves into cost analysis, regulatory issues, barriers to implementation, conversion and storage systems, thermodynamic efficiency, fuel chain efficiency, air emission issues, and safety. The book also covers natural gas hydrogen gas, methanol, ethanol, and steam reforming.
Keywords: Hydrogen as fuel.; Fuel switching.; Hydrogen cars.; Automobile industry and trade -- Forecasting.; elektronické knihy; electronic books